The Role of Femoroacetabular Impingement in Core Muscle Injury/Athletic Pubalgia: Diagnosis and Management - Strosberg, David S.; Ellis, Thomas J.; Renton, David B. (Frontiers in Surgery, 2016)
Chronic groin pain in athletes represents a major diagnostic and therapeutic challenge in sports medicine. Two recognized causes of inguinal pain in the young adult athlete are core muscle injury/athletic pubalgia (CMI/AP) and femoroacetabular impingement (FAI). CMI/AP and FAI were previously considered to be two distinct entities, however recent studies have suggested both entities to frequently coincide in the athlete with groin pain. This article briefly discusses the role of femoroacetabular impingement in core muscle injury/athletic pubalgia, and the diagnosis and management of this complex disease.